Isolation of an Antigen of Neisseria gonorrhoeae Involved in the Human Immune Response to Gonococcal Infection - Schmale, John D. (1969)
Ion-exchange chromatography was used to isolate a fraction from disrupted gonococci which reacts with sera from patients with gonococcal disease in complement-fixation and gel-diffusion tests. This antigenic fraction was shown to be the same as that previously described as having been isolated by gel filtration. The method reported here has the advantage of greater rapidity of isolation together with some improvement in purity.